Study of Petrogenesis Andesite Rock in Bualemo Region, North Gorontalo Regency Based on XRF Geochemistry Analysis - Fandji Marfian; Aang Panji Permana; Noviar Akase (Universitas Negeri Gorontalo, 2023)
The research area is Bualemo Village, Kwandang District, North Gorontalo Regency. With coordinates 0˚ 47' 10